Structure and dynamics of Penetratin?s association and translocation to a lipid bilayer - General, Ignacio (2017)
Penetratin belongs to the important class of small and positively charged peptides, capable of entering cells. The determination of the optimal peptidic structure for translocation is challenging; results obtained so far are varied and dependent on several factors. In this work, we review the dynamics of association of Penetratin with a modeled dioleoyl-phosphatidylcholine (DOPC) lipid membrane using molecular dynamics simulations with last generation force fields. Penetratin's structural preferences are determined using a Markov state model. It is observed that the peptide retains a helical form in the membrane associated state, just as in water, with the exception of both termini which lose helicity, facilitating the interaction of terminal residues with the phosphate groups on the membrane's outer layer. The optimal orientation for insertion is found to be with the peptide's axis forming a small angle with the interface, and with R1 stretching toward the bilayer. The interaction between arginine side-chains and phosphate groups is found to be greater than the corresponding to lysine, mainly due to a higher number of hydrogen bonds between them. The free energy profile of translocation is qualitatively studied using Umbrella Sampling. It is found that there are different paths of penetration, that greatly differ in size of free energy barrier. The lowest path is compatible with residues R10 to K13 leading the way through the membrane and pulling the rest of the peptide. When the other side is reached, the C-terminus overtakes those residues, and finally breaks out of the membrane. The peptide's secondary structure during this traversal suffers some changes with respect to the association structure but, overall, conserves its helicity, with both termini in a more disordered state.